Non-dual Reality and Empirical Existence in Advaita Vedānta and Ghazālī’s Metaphysics of Unity - Patrick Laude (19817643) (2024)
This essay explores the ways in which two distinct spiritual traditions, Ghazālī’s Ṣūfīsm and Śaṅkarian Advaita Vedānta, articulate an exclusive metaphysical affirmation of the Ultimate Reality with an empirical recognition of relative existence. Both perspectives are shown to be radically absolutist in their discernment of the Real and in their denying metaphysical reality to other-than-the-Absolute. This raises the question of the ontological status of relativity and empirical existence. Although Islam would seem to assign a greater reality to the world of relativity and human experience, Ghazālī’s most metaphysical treatise, Mishkāt al-anwār (The Niche of Lights), utterly denies the intrinsic reality of creatures in themselves. Similarly, Śaṅkara affirms the non-existence of māyā, the principle of ignorance and duality, as a superimposition upon ātman, the Divine Self immanent to all. Ghazālī concedes, however, that relative existence is “metaphorically” existent (majāz) while Śaṅkara acknowledges the “transactional” reality (vyāvahārika) of empirical existence. Such recognitions involve a multi-stratified view of reality that must account for both metaphysical consistency and empirical access to Reality. This essay shows that although fundamental parallels between the two worlds of meaning can be highlighted, their respective metaphysical perspectives and views of relativity are also quite distinct inasmuch as they are informed by profoundly different religious and traditional contexts. Other Information Published in: International Journal of Hindu Studies License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11407-024-09375-4